2018
DOI: 10.1136/annrheumdis-2018-214140
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patient-perceived and physician-perceived remission and low disease activity in psoriatic arthritis: an analysis of 410 patients from 14 countries

Abstract: BackgroundThe objective was to compare different definitions of remission and low disease activity (LDA) in patients with psoriatic arthritis (PsA), based on both patients’ and physicians’ perspectives.MethodsIn ReFlap (Remission/Flare in PsA; NCT03119805), adults with physician-confirmed PsA and >2 years of disease duration in 14 countries were included. Remission was defined as very low disease activity (VLDA), Disease Activity index for PSoriatic Arthritis (DAPSA) ≤4, and physician-perceived and patient-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 49 publications
7
39
1
5
Order By: Relevance
“…On the contrary, the best agreement was seen between cDAPSA remission and PASS. In this sense, our findings are quite consistent with those of the recently published ReFlap (Remission/Flare in PsA) study [16]. In ReFlap, adults with physician-confirmed PsA and > 2 years of disease duration in 14 countries were included.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, the best agreement was seen between cDAPSA remission and PASS. In this sense, our findings are quite consistent with those of the recently published ReFlap (Remission/Flare in PsA) study [16]. In ReFlap, adults with physician-confirmed PsA and > 2 years of disease duration in 14 countries were included.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, DAPSA-based remission/low disease activity (LDA) performed better than VLDA/MDA to detect patient defined remission or remission/LDA. Further, physicianperceived remission/LDA using a single question was frequent (67.6%) but performed poorly against other definitions [16]. Which are the drivers of this discordance between patient-perceived remission, or low impact of disease, and physician-defined remission?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the good sensitivity and specificity of PASS with respect to PsAID can be explained by the fact that both instruments are based on ‘subjective’ domains more than ‘objective’ ones, underlining that both instruments may capture the patient's perception of the disease. In this context, a similarity between PASS and patient-perceived low disease activity in the REFLAP study can be found 31. In conclusion, this study showed that PASS might be used as an alternative for assessment of low disease activity and overall disease status in patients with PsA in real clinical practice.…”
Section: Discussionsupporting
confidence: 62%
“…33 34 Remission in PsA is difficult to define. 33 Remission should be seen as abrogation of inflammation.…”
Section: Newmentioning
confidence: 99%